PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR DAN MINAT BELAJAR SISWA KELAS IV PEMBELAJARAN MATEMATIKA - Linda Natalia; Anita Trisiana; Mukhlis Mustofa (UNIVERSITAS SLAMET RIYADI, 2023)
The purpose of this study was to determine the effect of applying the problem-based learning model on learning outcomes and students’ learning interest in class IV in learning mathematics at SD N Joglo 76 Surakarta in 2023. This quantitative research has a design one group pretest-posttest design. The population were all students in class IV at SD N Joglo 76 Surakarta with a saturated sampling technique, the sample used was 28 students in class IVB. Data collection techniques were through observation, interviews, tests and questionnaires. Based on the test questions, the results of the t-count hypothesis was 12.608 with the value of t-table was d.b = (n-1) the result was (28-1) = 27 at the 5% significance level was 1.703. The normality test results t-count > t-table or 12.608 > 1.703. The average student questionnaire changed from the pretest to the posttest, 28.01 to 31.8. Based on the results of the simple linear regression test the F-count is 36.596 with a significance of 0.000 < 0.05. So, it could be concluded that there is an influence in using the problem-based learning model on learning outcomes and students’ reading interest in class IV in learning mathematics at SD N Joglo 76 Surakarta in 2023. Keywords: Problem-based Learning Model, Learning Outcomes, Interest in Learning